Strategi Pemasaran Media Sosial Destinasi Pariwisata Menggunakan Pendekatan SOSTAC: Studi Kasus Pada Akun Media Sosial Dinas Kebudayaan dan Pariwisata Kab. Lebak, Banten - Hidayah, Nurdin; Sopian, Tatang; Aziz M. Nauval; Feby Nur Ikrawardani; Flavia Domitilla Fausta; Inggit Salsabila Putri; M. Hafidz Annazly; Salma Nabila M (Politeknik Pariwisata NHI Bandung, 2021)
This study aims to optimize the social media performance of the Lebak Regency Culture and Tourism Office through the preparation of a social media marketing strategic plan. The research method uses an exploratory method with a qualitative approach. The data were obtained by conducting interviews with key informants, major informants and supporting informants using criterion sampling technique. Observations, document reviews, and literature studies were also carried out to confirm the validity of the data by triangulation. Data were analyzed using analytical techniques in accordance with the stages of social media marketing planning using the SOSTAC approach with SWOT analysis and social media analysis tools, namely Hootsuit, Socialblade, Facebook Analytic, Instagram Insight, and Youtube Studio (Youtube Analytic). This study produced 15 strategies, 21 tactics, and 24 action plans for social media marketing strategic plan.